Review of Gearbox Instantaneous Speed Measurement Methods Based on Vibration Signals - Lin Dong; Jia Shanhu; Zhang Erliang (Jixie chuandong)
In order to address the problems of installation inconvenience and high cost of traditional encoder for speed measurement, the estimation method of instantaneous speed of rotating machinery based on vibration acceleration is studied and summarized. The present work recapitulates the basic principles of six popular instantaneous speed estimation algorithms, investigates these six speed measurement methods through the speed test of industrial helical gearboxes under different working conditions, and analyzes their advantages and applicability. The results show that the vibration acceleration signal indirectly contains the speed information of the gearbox, which can be used to accurately estimate the instantaneous speed of the gearbox, and which is of great significance for the condition monitoring and control of the gearbox in operating conditions.